Women's careers in the Arab Middle East: Understanding institutional constraints to the boundaryless career view. Issue 3 (3rd June 2014) - Afiouni, Fida
Abstract : Purpose: – The purpose of this paper is to examine how women academics from the Arab Middle East enact their careers with reference to double-bounded contexts: academia as an institution encoding organizational career scripts and gender as another institution encoding specific gender roles. It is hoped that this cross-cultural perspective would broaden the understanding of careers beyond the economically advanced industrialized countries and better inform the current debate on the boundaryless career model. Design/methodology/approach: – The study is qualitative and exploratory in nature. It draws on one-to-one interviews with 23 female academics in early, mid and late careers, working in research universities in the Arab Middle East region. Findings: – The choice of academia as a profession is mainly driven by the subjective perception of an academic career as a calling, the lack of attractiveness of other career options in the region, and the appeal of the flexibility of academic work. Furthermore, the findings highlight both organizational (lack of mentoring and university support) and cultural factors (Islam, patriarchy, and family centrality) that shape/bind women's careers choices and patterns allowing thus for a better understanding of local constraints to the boundaryless career view in the Arab Middle East context. Originality/value: – The paper contributes to the boundaryless career theory development by addressing one of its major shortcomings, namely the lack of attention to context. It provides fresh insights from the Arab Middle East to the ongoing debate whether careers are boundaryless and subject to individual agency or whether careers are shaped by wider institutional factors and support existing calls in the literature to conceptualize careers at the intersection of several influencing factors.